The Structural and Catalytic Activity Studies of some iron (III) complexes of the Schiff bases derived from 3-Hydroxy-quinoxaline-2-carboxaldehyde with various amines (International Journal of Food and Nutritional Sciences, 2022)
Iron (III) complexes of four Schiff base ligands of 3-hydroxy-quinoxaline-2-carboxaldehyde with the amines ethylenediamine (QED), o-phenylenediamine (QPD), hydrazine hydrate (QHD) and diethylenetriamine (QDT) were synthesized and the characterization of the complexes were done by spectral, magnetic and conductance measurements. The catalytic activity of the complexes incorporated on Seralite SRC 120 resin as support were screened in the oxidation of the biologically important substrate vitamin C. All the supported complexes were found to be catalytically active in this reaction and were stable during the reaction. Two of the complexes with flexible ligands QED and QDT were more active towards this reaction, than the other two complexes